2018
DOI: 10.1016/j.physletb.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the full excitation spectrum of the 7Li(p,γ)αα reaction at 441 keV

Abstract: A current challenge for ab initio calculations is systems that contain large continuum contributions such as 8 Be. We report on new measurements of radiative decay widths in this nucleus that test recent Green's function Monte Carlo calculations.Traditionally, γ ray detectors have been utilized to measure the high energy photons from the 7 Li(p, γ)αα reaction. However, due to the complicated response function of these detectors it has not yet been possible to extract the full γ ray spectrum from this reaction.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Recent observation [1] of a light, neutral boson decaying into an e + e − pair with a mass of about 17 MeV, in the decay of the I(J π ) = 0(1 + ) state of 8 Be at Atomki, has generated a great deal of interest [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Supporting evidence for this hypothetical X17 particle has been reported recently in the decay of the excited I(J π ) = 0(0 − ) state of 4 He [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observation [1] of a light, neutral boson decaying into an e + e − pair with a mass of about 17 MeV, in the decay of the I(J π ) = 0(1 + ) state of 8 Be at Atomki, has generated a great deal of interest [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Supporting evidence for this hypothetical X17 particle has been reported recently in the decay of the excited I(J π ) = 0(0 − ) state of 4 He [16].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier observations of similar e + e − pairs with invariant masses between 3 to 20 MeV in the collision of nuclei with emulsion detectors have been reported [17][18][19][20][21][22]. Different theoretical interpretations, astrophysical implications, and experimental searches have been presented [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. However, a definitive description of the X17 particle has not yet emerged.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to reproducing the known 8 Be states, the SA-NCSM calculations also predict a low-lying, 2 + α + α state with a width of 10(3) MeV (calculated using a NNLO opt chiral potential) [29], which would be accessible to 8 Li via allowed β decay. There has been an ongoing debate about the existence of this so-called "intruder state," though experimental evidence remains inconclusive [21,25,[30][31][32][33][34][35][36][37]. This measurement was also unable to reach a conclusion on the intruder resonance's existence based on R-matrix fitting.…”
mentioning
confidence: 83%
“…These excitation energies agree with the SA-NCSM extrapolated results given the error bars [4], as well as with the predicted widths. In addition, a recent experimental study has found a tentative evidence for a broad 0 + state at 12 MeV, prompting a need for further measurements [17]. Various earlier ab initio studies have seen intruder 0 + and 2 + states as well [18][19][20].…”
Section: LI Beta Decaymentioning
confidence: 99%